2013
DOI: 10.5489/cuaj.506
|View full text |Cite
|
Sign up to set email alerts
|

Giant fibroepithelial polyp of the glans penis not associated with condom-catheter Use: A case report and literature review

Abstract: Fibroepithelial polyps are rare benign tumours of the glans penis; there are only a few reported cases. The pathogenesis is unknown. However, they have been linked with chronic condom catheter use or prior penile surgery. We report a case of a 62-year-old man with a large fibroepithelial polyp of the glans penis of 11 years duration, which was not associated with condom catheter use or prior surgery. The mass was large, measuring 7 × 5 × 3 cm. Fibroepithelial polyps have been reported in a range of genitourina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…Ghosh et al reported four cases with giant skin tags on unusual localizations including nipple (3x2.5 cm), eyelid (0.5x2 cm) and right thigh (2.5x2.5 cm) [2]. Yan et al reported a 62-year-old patient with a giant skin tag measuring 7x5x3 cm on penis with verrucous appearance [1]. Ilango et al described a giant skin tag measuring 12x8 cm on the back with variable pigmentation [4].…”
Section: Sirmentioning
confidence: 99%
See 3 more Smart Citations
“…Ghosh et al reported four cases with giant skin tags on unusual localizations including nipple (3x2.5 cm), eyelid (0.5x2 cm) and right thigh (2.5x2.5 cm) [2]. Yan et al reported a 62-year-old patient with a giant skin tag measuring 7x5x3 cm on penis with verrucous appearance [1]. Ilango et al described a giant skin tag measuring 12x8 cm on the back with variable pigmentation [4].…”
Section: Sirmentioning
confidence: 99%
“…It usually presents as a small, pedunculated polyp in intertriginous areas such as neck, axilla, groin and face. Rarely, skin tags may appear in the respiratory tract, orophyarynx, female and male genitalia [1,2]. Skin tags affect 46% of the general population.…”
Section: Sirmentioning
confidence: 99%
See 2 more Smart Citations
“…They are most commonly found in lower genitourinary tracts including lower glans penis, ureter, cervix, rectum, and in the anus. 1 When found in the perineum, these lesions are commonly referred to as skin tags. Most of these polyps remain smaller than 5 cm.…”
mentioning
confidence: 99%